2012
DOI: 10.1038/mt.2011.236
|View full text |Cite
|
Sign up to set email alerts
|

Functionally Enhanced siRNA Targeting TNFα Attenuates DSS-induced Colitis and TLR-mediated Immunostimulation in Mice

Abstract: Tumor necrosis factor (TNFα) is a proinflammatory cytokine involved in the pathogenesis of inflammatory bowel disease (IBD). Although TNFα has been extensively targeted using systemic drugs, the use of antisense and small interfering RNA (siRNA) to drive down its expression at the site of inflammation should provide important advantages. In this study, native and chemically modified siRNA against TNFα was developed and characterized using a murine model of IBD. siRNA with 2'-O-methyl and propanediol modificati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 46 publications
1
16
0
Order By: Relevance
“…The absence or inhibition of TNF activity ameliorates disease progression in different experimen-tal IBD models and in human patients. Treatment with a TNF neutralizing antibody, a locally active TNF inhibitor, antisense oligonucleotides and siRNA molecules specific for TNF were shown to be effective in the DSS-induced colitis model (Dharmani et al, 2011;Murthy et al, 2002;Myers et al, 2003;Ocampo et al, 2012). As expected, we observed that MMP13 À/À mice were less sensitive to DSS-induced colitis than MMP13 þ/þ mice and that this was correlated with reduced bioactive TNF levels.…”
Section: Discussionsupporting
confidence: 80%
“…The absence or inhibition of TNF activity ameliorates disease progression in different experimen-tal IBD models and in human patients. Treatment with a TNF neutralizing antibody, a locally active TNF inhibitor, antisense oligonucleotides and siRNA molecules specific for TNF were shown to be effective in the DSS-induced colitis model (Dharmani et al, 2011;Murthy et al, 2002;Myers et al, 2003;Ocampo et al, 2012). As expected, we observed that MMP13 À/À mice were less sensitive to DSS-induced colitis than MMP13 þ/þ mice and that this was correlated with reduced bioactive TNF levels.…”
Section: Discussionsupporting
confidence: 80%
“…The absence or inhibition of TNF activity ameliorates disease progression in different experimental IBD models and in human patients. Treatment with a TNF neutralizing antibody, a locally active TNF inhibitor, antisense oligonucleotides and siRNA molecules specific for TNF were shown to be effective in the DSS‐induced colitis model (Dharmani et al, ; Murthy et al, ; Myers et al, ; Ocampo et al, ). As expected, we observed that MMP13 −/− mice were less sensitive to DSS‐induced colitis than MMP13 +/+ mice and that this was correlated with reduced bioactive TNF levels.…”
Section: Discussionmentioning
confidence: 99%
“…Lipoplex-siRNA-2 is an enema containing liposomal, chemically modified siRNA against TNF-α [ 135 ]. Chemically modifying siRNA may increase the silencing capacity, resistance to degradation or both.…”
Section: Preclinical Studies On Local Tnf-α Inhibitionmentioning
confidence: 99%